2016
DOI: 10.1128/genomea.00855-16
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Insights into Aquimarina sp. Strain EL33, a Bacterial Symbiont of the Gorgonian Coral Eunicella labiata

Abstract: To address the metabolic potential of symbiotic Aquimarina spp., we report here the genome sequence of Aquimarina sp. strain EL33, a bacterium isolated from the gorgonian coral Eunicella labiata. This first-described (to our knowledge) animal-associated Aquimarina genome possesses a sophisticated repertoire of genes involved in drug/antibiotic resistance and biosynthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…With exception of Aquimarina sp. Aq107, closely related to A. latercula and A. versatilis , all Aquimarina strains retrieved from marine invertebrates (sponges and corals) in the Northeast Atlantic (Esteves et al ., ; Keller‐Costa et al ., , ) affiliated with the A. atlantica ‐ megaterium ‐ macrocephali 16S rRNA gene clade depicted here, which also included several strains retrieved from seawater (Supporting Information Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With exception of Aquimarina sp. Aq107, closely related to A. latercula and A. versatilis , all Aquimarina strains retrieved from marine invertebrates (sponges and corals) in the Northeast Atlantic (Esteves et al ., ; Keller‐Costa et al ., , ) affiliated with the A. atlantica ‐ megaterium ‐ macrocephali 16S rRNA gene clade depicted here, which also included several strains retrieved from seawater (Supporting Information Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
“…Of these genomes, five belong to an in‐house collection of symbionts of octocorals and marine sponges: Aquimarina sp. EL33, Aq78, Aq107, Aq135 and Aq349 (Esteves et al ., ; Keller‐Costa et al ., , ) and the remainder originate from seawater, marine sediments and algae (Table ). Strain Aq349 is the source of the recently described trans ‐AT polyketide cuniculene (Helfrich et al ., ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… Unknown –Zooxanthellate corals: coral– Symbiodinium symbiosis [ 20 , 82 , 93 , 94 , 121 ] Bacteroidetes Flavobacteriia Flavobacteriales Flavobacteriaceae Aquimarina Antillogorgia elisabethae Eunicella spp. Leptogorgia sarmentosa Nutrient cycling Nitrogen cycling (denitrification) Carbon cycling (chitin degradation) Sulfur cycling (sulphate reduction) Microbiome regulation [ 20 , 89 , 101 ] Chlamydiae Chlamydiae Chlamydiales Simkaniaceae Candidatus Fritschea Eunicella spp. Leptogorgia sarmentosa Unknown [ 20 , 76 ] Parcubacteria Corallium rubrum Unknown [ 20 , 83 ] Proteobacteria Alphaproteobacteria Rickettsiales Rickettsiales incertae sedis Candidatus Lariskella Eunicella spp.…”
Section: Bacteriamentioning
confidence: 99%
“…Another genus specialized for survival in oligotrophic conditions and commonly associated with a tropical [ 89 ] and various temperate gorgonians [ 20 ] is Aquimarina . Genome analysis of an Aquimarina symbiont isolated from Eunicella labiata [ 101 ] has revealed that it possesses a remarkable capacity to cycle nutrients: nitrogen (denitrification), sulfur (assimilatory sulphate reduction), and carbon (chitin degradation). In addition, it has a large arsenal of genes related to defense as well as for the production of antimicrobial compounds.…”
Section: Bacteriamentioning
confidence: 99%